Pola Asuh Orang Tua dan Interaksi Sosial Siswa Sekolah Dasar : Sebuah Kajian Literatur - Firdausiyyah, Kunti Zakiyyatal (FKIP Universitas Islam Jember, 2025)
Home is the first school for children. Not only that, home is also a place for children to learn everything about the world. Starting from how to learn, how to make friends, to how to socialize. Children not only learn to know their parents at home, but more than that, home also determines the success of children interacting at school. Because the model of children interacting is one of them seen from their parents. The purpose of this study was to determine the synthesis of research results regarding the influence of parenting patterns on children's social interactions at school. This study was conducted by conducting a literature study, by filtering articles that had been searched based on previously determined keywords. The results of this study indicate that there is a significant influence between parenting patterns and children's social interactions at the elementary school level. Therefore, parents must take the time and attention to understand their children, so that children can have healthy social interaction patterns at school and this will support children's learning outcomes.